Triathlon & Endurance Sports - Coste O (Dynamic Media Sales Verlag, 2020)
Regular physical activity is now considered as a therapeutic per se for sedentary people or those with chronic diseases, and learned societies of sports medicine have developed the mantra Exercise is medicine. However, despite the overwhelming evidence of its benefits on health and prevention of non-communicable diseases, there is still a gap between scientific data and development of exercise-based prevention program in the general population, or in clinical setting.The path for the recognition of sports as a major contributor to health and wellbeing has been difficult for government authorities, healthcare providers, and federal sports authorities, because of many economical and medical barriers. Awareness and involvement of sports federations may help to reduce those barriers and fill this gap.Although its still often mistakenly considered a superhuman sport, triathlon brings together 3 sports disciplines frequently recommended for people wishing to begin regular physical activity, and thus seems to be an interesting choice as a sport for health for most people/patients. After recalling the national sport and health strategy 2019-2024 developed for Paris Olympics, we report here the four steps of the Health Triathlon program implemented by the French Triathlon Federation, to illustrate the main framework, the feasibility, first results and benefits for participants of this initiatives. Key Words: Sedentary Behaviour, Chronic Diseases, Evaluation, Prevention